Low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst and preparation method and use thereof
By preparing a low Pt-(Ni-NiO) nanosphere catalyst with low Pt load on carbon cloth fibers, laser ablation is used to form a core-shell structure and impregnate Pt single atoms, the problems of Pt resource scarcity and insufficient electronic conductivity of NiO are solved. , efficient and stable electrolytic hydrogen production catalyst is achieved, reducing costs and improving electrocatalytic activity.
Patent Information
- Application Number
- CN202411303397.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The scarcity and high cost of Pt in existing electrolytic hydrogen production catalysts limit their industrial application, and the electron conductivity of NiO is poor and the hydrogen adsorption energy is too low, which hinders the further improvement of catalyst activity.
Using the preparation method of low Pt-supported Pt-(Ni-NiO) nanospheres @ carbon cloth fiber catalyst, Ni(OH)2 nanosheets were grown in situ on carbon cloth fibers by nickel nitrate and dimethylimidazole methanol solution, using Carbon dioxide laser ablation forms a Ni-NiO core-shell structure and impregnates Pt single atoms on it to form a self-supported core-shell structure to improve electron conductivity and active sites.
The high-efficiency electrocatalytic activity and long-term stability of low Pt-supported catalysts under high current density is achieved, which reduces the cost of electrode preparation, significantly improves the basic HER activity and stability, and is better than commercial Pt/C catalysts.
Smart Images

Figure CN118814217B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen production by water electrolysis can convert green electricity generated by solar energy and wind energy into hydrogen energy storage, and is expected to solve the problem of difficulty in integrating wind and solar power generation into the power grid. Due to the sluggish kinetics of the hydrogen evolution reaction (HER), an efficient catalyst is required to promote the reaction. Although significant progress has been made in the application of non-precious metal catalysts in HER, Pt is still the most ideal catalyst material for HER at present, because its H atom adsorption position is close to the center of the "volcano curve", thus having excellent intrinsic hydrogen evolution activity. However, the scarcity and high cost of Pt resources limit its practical application. Therefore, reducing the Pt content in the catalyst and increasing the number of active sites are the key to realizing the industrial-scale application of Pt-based catalysts for water electrolysis.
[0003] Compared with nanoparticle catalysts, single atom and cluster catalysts have attracted attention due to their high atomic utilization and high intrinsic activity. Single atom catalysts can maximize the dispersion of metal elements while reducing the amount of metal and thus reducing costs. For the Pt single atoms reported so far, the introduction of strong electronic metal-support interaction (EMSI) to fix Pt single atoms on the support surface is considered to be a promising method to regulate the local electronic interaction between the Pt center and the support. This interaction is usually achieved by establishing Pt bonds with neighboring atoms on the support, which changes the charge density distribution of the Pt single atom, thereby optimizing its catalytic performance. Classical EMSI mainly occurs on metal oxide supports such as (NiO, CeO2, TiO2 and Co3O4). Among them, NiO has a strong adsorption capacity for *OH intermediates, which is conducive to the dissociation of H2O, and is therefore a promising support material. However, the inherent poor electronic conductivity and low hydrogen adsorption energy of NiO itself hinder the further improvement of catalyst activity. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a Pt-(Ni-NiO) nanosphere @ carbon cloth fiber catalyst with low Pt loading. The prepared catalyst has the advantages of abundant defects, highly exposed active sites, excellent electronic conductivity and rapid charge transfer at low Pt loading, thereby showing high electrocatalytic activity and excellent long-term stability at high current density, providing a reliable strategy for the design, preparation and wide application of efficient electrocatalytic hydrogen evolution electrodes. One of the purposes of the present invention is to provide a method for preparing a Pt-(Ni-NiO) nanosphere @ carbon cloth fiber catalyst with low Pt loading. The prepared catalyst has the advantages of abundant defects, highly exposed active sites, excellent electronic conductivity and rapid charge transfer at low Pt loading, thereby showing high electrocatalytic activity and excellent long-term stability at high current density, providing a reliable strategy for the design, preparation and wide application of efficient electrocatalytic hydrogen evolution electrodes.
[0005] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst, comprising the following steps:
[0006] S1. Pre-treating the carbon cloth to obtain a clean and hydrophilic surface;
[0007] S2, uniformly dissolving Ni(NO3)2·6H2O in methanol to form solution 1; uniformly dissolving 2-methylimidazole in methanol to form solution 2; mixing solution 1 and solution 2 to obtain a mixed solution;
[0008] The carbon cloth pretreated in step S1 is immersed in the mixed solution, and after reacting at room temperature, it is taken out, washed and dried, and Ni(OH)2 nanosheets are in situ grown on the carbon cloth fibers;
[0009] S3, the carbon cloth on which the Ni(OH)2 nanosheets are grown is treated with a carbon dioxide laser at a frequency of 25-40 KHz, a processing speed of 200-300 m / s, a line spacing of 0.1-1 mm, and a laser power of 3 W-12 W, to obtain Ni-NiO core-shell nanospheres on the carbon cloth fibers, wherein NiO is the shell and Ni is the core;
[0010] S4. The carbon cloth on which the Ni-NiO core-shell nanospheres are grown is immersed in an H2PtCl6 aqueous solution for a period of time, then taken out, washed and dried, to finally obtain a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst, in which Pt single atoms are loaded on the Ni-NiO core-shell nanospheres to form Pt-(Ni-NiO) nanospheres, and the Pt-(Ni-NiO) nanospheres are loaded on the carbon cloth fibers.
[0011] Further improvement of the preparation method of Pt-(Ni-NiO) nanospheres@carbon cloth fiber catalyst with low Pt loading:
[0012] Preferably, in step S1, the carbon cloth is ultrasonically treated in acetone, ethanol and deionized water for 10-30 minutes in sequence, and then immersed in 2-6 M nitric acid for 10-20 hours to obtain a clean and hydrophilic surface.
[0013] Preferably, in step S2, the dissolved concentration of Ni(NO3)2·6H2O in solution 1 is 0.1-0.4 mg / mL, the dissolved concentration of 2-methylimidazole in solution 2 is 0.05-0.2 mg / mL, and the mass ratio of Ni(NO3)2·6H2O and 2-methylimidazole in the mixed solution is (2-4):1.
[0014] Preferably, in step S2, 10.46 mg of Ni(NO3)2·6H2O is uniformly dissolved in 40 mL of methanol to form solution 1, 3.94 mg of 2-methylimidazole is uniformly dissolved in 40 mL of methanol to form solution 2, and solution 1 and solution 2 are mixed in a volume ratio of 1:1 to obtain a mixed solution.
[0015] Preferably, in step S2, the size of the pretreated carbon cloth is (1-3) cm×(3-6) cm, and it is immersed in 20-40 mL of the mixed solution and reacted at room temperature for 12-24 h.
[0016] Preferably, the concentration of the H2PtCl6 aqueous solution in step S4 is 0.2-0.5 mg / mL and the volume is 6-10 mL.
[0017] Preferably, in step S4, the carbon cloth on which the Ni-NiO core-shell nanospheres are grown is immersed in an aqueous H2PtCl6 solution at a temperature of 50-60°C for a time of 2-10 h.
[0018] Preferably, deionized water is used for washing in steps S2 and S4, and the drying temperature is 50-60° C. and the drying time is 12-20 h.
[0019] The second object of the present invention is to provide a low Pt-loaded Pt-(Ni-NiO) nanosphere @ carbon cloth fiber catalyst obtained by the preparation method of the low Pt-loaded Pt-(Ni-NiO) nanosphere @ carbon cloth fiber catalyst described in any of the above items.
[0020] The third object of the present invention is to provide an application of the above-mentioned low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst in hydrogen production by water electrolysis.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention combines laser ablation with impregnation adsorption process to provide a method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst, comprising: using nickel nitrate and dimethylimidazole methanol solution as precursor solution, and using a room temperature liquid phase method to in situ grow high-density Ni(OH)2 nanosheets on carbon cloth fiber cloth; then, using laser ablation treatment to obtain a core-shell structured Ni-NiO nanosphere array; subsequently, immersing the Ni-NiO nanospheres in a H2PtCl6 solution for a period of time, and finally washing and drying to obtain a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst.
[0023] Among them, carbon dioxide laser treatment is used. Since laser ablation will produce a transient high temperature and high pressure environment, Ni-NiO with a core-shell structure is obtained. The constructed metal Ni and semiconductor NiO form a Mott-Schottky junction in situ, which is conducive to electron transfer; large stress distortion, rich defects and oxygen vacancies are generated inside the shell NiO material, which not only exposes more active sites, but also increases the electronic conductivity of NiO, increases the number of electrochemical active sites, thereby improving the catalytic activity, and can also firmly anchor Pt single atoms on its surface through strong electronic metal-support interaction (EMSI), significantly improving the alkaline HER activity and stability of the catalyst when used as an electrode. At the same time, Ni-NiO-Pt nanospheres grow firmly on carbon cloth to form a self-supporting, structurally integrated structure, which greatly improves the stability of the catalyst as an electrode, so that the catalyst electrode has good durability and fast charge transfer rate. The preparation process of the present invention is simple, and while making full use of precious metal materials, it can greatly reduce the preparation cost of the electrode.
[0024] (2) The Pt-(Ni-NiO) nanosphere@carbon fiber catalyst with low Pt loading prepared by the present invention has a Pt single atom loading of about 3.3 wt% (loading per unit area of about 23 ug cm -2 ) and good dispersibility, and when used as an integrated self-supporting electrode for efficient and stable water electrolysis to produce hydrogen, in 1.0 M KOH electrolyte, only 23.88 mV overpotential is required to drive 10 mA cm -2 The current density is only 236.52 mV, which is enough to drive 500 mA cm -2 The present invention has a current density of 10000 Å, a small Tafel slope and excellent long-term stability, and has an alkaline HER performance superior to that of commercial Pt / C at a high current density. The technical solution of the present invention provides a promising approach for the design of efficient and stable alkaline HER catalyst electrodes, and opens up new ideas for the research and development of air batteries, supercapacitors and other advanced electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the XRD pattern of Pt-(Ni-NiO)@C-1 prepared in Example 1.
[0026] Figure 2 It is a structural characterization diagram of Pt-(Ni-NiO)@C-1 prepared in Example 1; (a) and (b) are SEM images at different magnifications; (c) is a TEM image; (d) is a HRTEM image; (e) is a STEM image; (f) is a HAADF-STEM image; (g), (h), (i), and (j) are the element distributions corresponding to C, Ni, O, and Pt, respectively.
[0027] Figure 3 This is the electron paramagnetic resonance image of Pt-(Ni-NiO)@C-1 prepared in Example 1.
[0028] Figure 4 (a) is the Ni 2p XPS spectrum of the Ni-NiO core-shell nanospheres and Pt-(Ni-NiO)@C-1 prepared in Example 1; (b) is the O 1s XPS spectrum of the Ni-NiO core-shell nanospheres and Pt-(Ni-NiO)@C-1 prepared in Example 1; (c) is the Pt 4f XPS spectrum of Pt-(Ni-NiO)@C-1 prepared in Example 1.
[0029] Figure 5 This is a comparison chart of the LSV curve performance of Pt-(Ni-NiO)@C-1, Pt-(Ni-NiO)@C-2, and Pt-(Ni-NiO)@C-3 as electrodes prepared under different H2PtCl6 immersion times in Examples 1-3, where vs. RHE represents the voltage obtained relative to the standard hydrogen electrode RHE.
[0030] Figure 6 This is a comparison chart of the LSV curve performance of Pt-(Ni-NiO)@C-1, Pt-(Ni-NiO)@C-4, and Pt-(Ni-NiO)@C-5 as electrodes prepared using different laser powers in Examples 1, 4, and 5.
[0031] Figure 7 HER electrocatalytic test graphs of Pt-(Ni-NiO)@C-1, commercial Pt / C, Pt-Ni(OH)2@C, (Ni-NiO)@C, Ni(OH)2@C and CC prepared in Example 1 and Comparative Example; (a) is the LSV curve after 90% iR compensation; (b) is the overpotential comparison; (c) is the Tafel slope; (d) is the double-layer capacitance; (e) is the Pt-(Ni-NiO)@C-1 prepared in Example 1 at 500 mA cm -2The stability diagram below.
[0032] Figure 8 TOF diagram of Pt-(Ni-NiO)@C-1 and commercial Pt / C prepared in Example 1. TOF represents the number of H2 molecules generated per unit time at a Pt active site. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] This embodiment provides a method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst, which specifically comprises the following steps:
[0036] S1, size 2×4 cm -2 The carbon cloth was ultrasonicated in acetone, ethanol and deionized water for 10 min respectively, and then immersed in 6 M nitric acid for 10 h to obtain a clean and hydrophilic surface;
[0037] S2, dissolving 10.46 mg Ni(NO3)2·6H2O in 40 mL methanol to form solution 1, dissolving 3.94 mg 2-methylimidazole in 40 mL methanol to form solution 2, and mixing solution 1 and solution 2 in a volume ratio of 1:1 to obtain a mixed solution;
[0038] Take 20 ml of the mixed solution, immerse the carbon cloth pretreated in step S1 into it, react at room temperature for 24 hours, then take out, wash and dry, and in-situ grow Ni(OH)2 nanosheets on the carbon cloth fibers;
[0039] S3, the carbon cloth on which the Ni(OH)2 nanosheets were grown was treated with a carbon dioxide laser (laser marking machine produced by Shanghai Sanke Laser Technology Co., Ltd., model SK-MARKER, total power of 30 W), with a frequency of 25 KHz, a processing speed of 200 m / s, a line spacing of 0.1 mm, and a laser power of 25% of the total power, to obtain Ni-NiO core-shell nanospheres on the carbon cloth fibers, in which NiO was the shell and Ni was the core;
[0040] S4. The carbon cloth on which Ni-NiO core-shell nanospheres were grown was immersed in 6 mL of H2PtCl6 aqueous solution (concentration of 0.2 mg / mL), immersed at 60 °C for 6 h, then taken out, washed with deionized water, and dried at 60 °C for 12 h to obtain a low Pt-loaded Pt-(Ni-NiO) nanospheres@carbon cloth fiber catalyst, recorded as Pt-(Ni-NiO)@C-1.
[0041] Under the concentration and immersion time of the H2PtCl6 solution in the above embodiment, the Pt loading in the prepared catalyst was determined to be about 3.3% and the loading per unit area was about 23 ug cm-1 by inductively coupled plasma emission spectroscopy. -2 .
[0042] Example 2
[0043] This embodiment provides a method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst. The specific steps are referred to in Example 1, except that in step S4, the carbon cloth on which the Ni-NiO core-shell nanospheres are grown is immersed in an H2PtCl6 aqueous solution for 3 h at 60°C. Finally, a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst is obtained, which is recorded as Pt-(Ni-NiO)@C-2.
[0044] Example 3
[0045] This embodiment provides a method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst. The specific steps are referred to Example 1, except that in step S4, the carbon cloth growing Ni-NiO core-shell nanospheres is immersed in an H2PtCl6 aqueous solution for 9 h at 60°C. Finally, a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst is obtained, which is recorded as Pt-(Ni-NiO)@C-3.
[0046] Example 4
[0047] This embodiment provides a method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon fiber catalyst. The specific steps are referred to in Example 1, except that the power of the carbon dioxide laser in step S3 is 10% of the total power. Finally, a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon fiber catalyst is obtained, which is recorded as Pt-(Ni-NiO)@C-4.
[0048] Example 5
[0049] This embodiment provides a method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon fiber catalyst. The specific steps are referred to in Example 1, except that the power of the carbon dioxide laser in step S3 is 40% of the total power. Finally, a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon fiber catalyst is obtained, which is recorded as Pt-(Ni-NiO)@C-5.
[0050] Comparative Example
[0051] This embodiment provides a method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst. The specific steps are referred to in Example 1, except that the Ni(OH)2 nanosheets prepared in step S2 are not subjected to the carbon dioxide laser treatment in step S3, but directly enter step S4. Finally, a Pt-loaded Ni(OH)2 nanosheet@carbon cloth fiber catalyst is obtained, which is recorded as Pt-Ni(OH)2@C.
[0052] Performance Testing
[0053] (1) Electrode morphology and structural characterization
[0054] The samples were characterized by transmission scanning electron microscopy (SEM), electron microscopy (TEM), X-ray diffraction spectroscopy (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FE-SEM), X-ray energy dispersive spectroscopy (EDS), atomic resolution aberration-corrected scanning transmission electron microscopy (AC-STEM) and electron paramagnetic resonance (EPR) techniques.
[0055] The Pt-(Ni-NiO)@C-1 electrode prepared in Example 1 was characterized by XRD to obtain the structural and chemical composition information of the sample. Figure 1 As shown. The clear diffraction peaks at 37.24°, 43.27°, 62.87°, 75.41° and 79.40° correspond to the (1 1 1), (2 0 0), (2 2 0), (3 1 1) and (2 2 2) crystal planes of NiO. The diffraction peaks at 44.50°, 51.84° and 76.37° belong to the (1 1 1), (2 0 0) and (2 2 0) crystal planes of Ni, respectively. No diffraction peaks of Pt were found, which indicates that no large Pt nanoparticles are formed in Pt-(Ni-NiO)@C-1, which means that Pt may exist in the form of single atoms in Pt-(Ni-NiO)@C-1.
[0056] Figure 2It is a structural characterization diagram of Pt-(Ni-NiO)@C-1 prepared in Example 1; (a) and (b) are SEM images at different magnifications; (c) is a TEM image; (d) is a HRTEM image; (e) is a STEM image; (f) is a HAADF-STEM image; (g), (h), (i), and (j) are the element distributions corresponding to C, Ni, O, and Pt, respectively. Figure 2 The SEM image in (a) shows that a large number of nanospheres are uniformly grown on the carbon cloth fiber cloth, and the average diameter of the nanospheres is about 300 nm; the local magnified SEM image shows that the nanospheres have a Ni-NiO core-shell structure and are tightly attached to the carbon cloth skeleton. A large number of nanoscale NiO spherical particles are surrounded on the surface and around the nanospheres ( Figure 2 (b)). Transmission electron microscopy (TEM) further characterized the morphology and composition of the Pt-(Ni-NiO)@C-1 electrode, as shown in Figure 2 As shown in (c), the Pt-(Ni-NiO)@C-1 electrode exhibits a unique core-shell structure. High-resolution TEM (HRTEM) images show a clear interface ( Figure 2 (d) The lattice spacing in the left region is 0.203 nm, which matches well with the (1 1 1) plane of Ni, while the lattice spacing in the right region is 0.240 nm and 0.208 nm, corresponding to the (111) and (2 0 0) planes of NiO, respectively. Atomic-resolution aberration-corrected scanning transmission electron microscopy (AC-STEM) images show isolated Pt atoms and obvious defects such as dislocations and vacancies on NiO ( Figure 2 (e)). High-angle annular dark field STEM (HAADF-STEM) images more clearly reveal the structure of Pt-(Ni-NiO)@C-1 ( Figure 2 (f)). The element distribution diagram shows that Ni is mainly distributed in the inner core, while O and Pt are evenly distributed in the outer layer ( Figure 2 (g), (h), (i), (j)), further confirming the successful preparation of Pt-(Ni-NiO)@C-1, and the Pt atoms are anchored in the outer layer of NiO.
[0057] The oxygen vacancies of Pt-(Ni-NiO)@C-1 prepared in Example 1 were measured by electron paramagnetic resonance (EPR). Figure 3 As shown in Figure 2, the resonance signal near the g value of 2.003 is caused by oxygen vacancies. After Pt atoms modify Ni-NiO, the EPR resonance peak intensity increases significantly, which may be due to the introduction of Pt atoms inducing the formation of more oxygen vacancies.
[0058] In order to clarify the effect of oxygen vacancies and platinum atoms on the surface chemical state, the Ni-NiO core-shell nanospheres and Pt-(Ni-NiO)@C-1 prepared in Example 1 were characterized by X-ray photoelectron spectroscopy (XPS). Figure 4 As shown in (a), Ni2p 3 / 2 The peaks at 854.2 eV and 871.5 eV belong to Ni 2+ , Ni 2p 3 / 2 The binding energies of 855.9 eV and 873.3 eV belong to Ni 3+ , and their satellite peaks are 861.4 eV and 879.8 eV, respectively, indicating that there is a nickel oxide layer on the surface of Pt-(Ni-NiO)@C-1. 3+ The signal can be attributed to the Ni vacancies in the lattice, which can create additional electrochemically active sites and thus enhance the HER performance. Figure 4 (b) is the XPS spectrum of O 1s. The peaks at 529.9 eV, 531.6 eV, and 533.2 eV correspond to lattice O, oxygen vacancies, and adsorbed OH. In addition, O 1s exhibits an obvious negative shift of about 0.2 eV after loading Pt, which may be due to the charge redistribution at the Pt-(Ni-NiO)@C-1 interface, resulting in electron transfer from Pt to NiO, which provides an important basis for the electronic interaction between NiO and Pt atoms. The XPS spectrum of Pt 4f is shown in Figure 2. Figure 4 As shown in (c), the peaks centered at 72.6 eV and 76.0 eV belong to Pt 2+ Pt 4f 7 / 2 and 4f 5 / 2 , the peaks centered at 74.2 eV and 77.7 eV belong to Pt 4+ Pt 4f 7 / 2 and 4f 5 / 2 No zero-valent metal peak was found in Pt4f, indicating that there were no aggregated nanoparticles in Pt-(Ni-NiO)@C-1.
[0059] (2) Hydrogen evolution performance test and analysis
[0060] A standard three-electrode test system was used, with 1.0 M KOH as the electrolyte, Hg / HgO electrode as the reference electrode, graphite rod electrode as the counter electrode, carbon cloth pretreated in Example 1 (denoted as CC), Ni(OH)2 nanosheets prepared on carbon cloth fibers in step S2 of Example 1 (denoted as Ni(OH)2@C), Ni-NiO core-shell nanospheres prepared on carbon cloth fibers in step S3 of Example 1 (denoted as (Ni-NiO)@C), Pt-(Ni-NiO)@C-1 prepared in Example 1, Pt-Ni(OH)2@C prepared in the comparative example, and commercial Pt / C catalyst (20 wt.%) were used as working electrodes in turn to test HER performance. At the same time, at 5 mV s -1 Linear sweep voltammetry (LSV) tests were performed at a rate of 0.01 Hz to 100 kHz, electrochemical impedance spectroscopy (EIS) tests were performed in the frequency range of 0.01 Hz to 100 kHz, and electrochemically active surface area (ECSA) was measured at 5 mV s -1 , 10 mV s -1 , 15 mV s -1 , 20 mV s -1 , 25mV s -1 and 30 mV s -1 The non-Faradaic range at the scan rate was determined by cyclic voltammetry (CV) curves, and the chronopotentiometry was used at 500 mA cm -2 The stability test was carried out at a constant current density.
[0061] Figure 5 This is a comparison chart of the LSV curve performance of Pt-(Ni-NiO)@C-1, Pt-(Ni-NiO)@C-2, and Pt-(Ni-NiO)@C-3 as electrodes prepared under different H2PtCl6 immersion times in Examples 1-3. Figure 5 The LSV curves show that the electrode performance of Pt-(Ni-NiO)@C-1 prepared in Example 1 is better than that of Pt-(Ni-NiO)@C-2 prepared in Example 2 and Pt-(Ni-NiO)@C-2 prepared in Example 3.
[0062] Figure 6 This is a comparison chart of the LSV curve performance of Pt-(Ni-NiO)@C-1, Pt-(Ni-NiO)@C-4, and Pt-(Ni-NiO)@C-5 as electrodes prepared using different laser powers in Examples 1, 4, and 5. Figure 6 The LSV curves show that the performance of the Pt-(Ni-NiO)@C-1 electrode prepared in Example 1 is better than that of the Pt-(Ni-NiO)@C-4 prepared in Example 4 and the Pt-(Ni-NiO)@C-5 prepared in Example 5.
[0063] Linear sweep voltammetry (LSV) curve ( Figure 7 (a) shows that the HER activity of Pt-(Ni-NiO)@C-1 electrode is much better than that of other synthesized electrodes and even better than that of commercial Pt / C catalyst. -2 , 100 mA cm -2 and 500 mA cm -2 The overpotentials under the conditions are only 23.88 mV, 86.03 mV and 236.52 mV respectively. Figure 7 (b)), which are all lower than Pt / C (37.57, 129.68, 290.78 mV). Compared with Pt-(Ni-NiO)@C-1, (Ni-NiO)@C has poor electrocatalytic activity for HER, confirming that the improvement of Pt-(Ni-NiO)@C-1 for HER electrocatalytic activity is mainly due to the presence of Pt species. In addition, at the same current density, the performance of Pt-(Ni-NiO)@C-1 is significantly better than that of Pt-Ni(OH)2@C, which indicates that the lattice distortion produced during laser irradiation can not only provide additional specific surface area and improve its electronic conductivity, but also the defects and oxygen vacancies produced during laser ablation firmly anchor Pt single atoms through strong electronic metal-support interaction (EMSI) to form highly active sites. Under the above synergistic effect, the HER catalytic activity of Pt-(Ni-NiO)@C-1 is significantly improved. In order to gain a deeper understanding of HER dynamics, Figure 7 (c) shows the Tafel slope corresponding to the polarization curve. In the low current density region, the Tafel slope of the Pt-(Ni-NiO)@C-1 electrode is 46.08 mV dec. -1 , even better than commercial Pt / C (51.37 mV dec -1 ), but the difference is relatively small. At the same time, at high current density, the Tafel slope of the Pt-(Ni-NiO)@C-1 electrode is only 108.72 mV dec -1 , which is much better than Pt-Ni(OH)2@C (183.36 mV dec -1 ) and (Ni-NiO)@C(214.38 mV dec -1 ), even better than Pt / C (128.80 mV dec -1 ), which indicates that the Pt-(Ni-NiO)@C-1 electrode has a higher electrode reaction rate at high current density. In addition, the double layer capacitance (C dl ) The estimated electrochemical active surface area (ECSA) is an important indicator for evaluating HER performance. dl Larger electrocatalysts have better HER performance. Figure 7As shown in (d), the C dl 38.53 mFcm -2 , higher than Pt / C (30.07 mF cm -2 ), Pt-Ni(OH)2@C (17.16 mF cm -2 ), (Ni-NiO)@C (10.16 mF cm -2 ) and Ni(OH)2 (6.07 mF cm -2 ), indicating that Pt-(Ni-NiO)@C-1 exposes more active sites. At the same overpotential, the larger ECSA of Pt-(Ni-NiO)@C-1 can be attributed to the exposure of more active sites caused by lattice distortion and highly dispersed Pt single atoms. Figure 7 As shown in (e), at 500 mA cm -2 The stability of the prepared samples was evaluated by constant current test at a constant current density of 500 mA cm -2 After 75 hours of continuous testing at the current density, the potential of the Pt-(Ni-NiO)@C-1 electrode increased by only 28 mV, indicating that it exhibits excellent long-term stability even at high current density.
[0064] For single-atom model catalysts, TOF can be used as a reliable basis for evaluating the intrinsic activity of catalysts. Figure 8 The TOF-overpotential curves of Pt-(Ni-NiO)@C-1 and commercial Pt / C prepared in Example 1. Figure 8 It can be seen that when the overpotential is 0.1 V, the TOF value of Pt-(Ni-NiO)@C-1 is 5.69 s -1 , is Pt / C (0.37 s -1 ), it can be seen that the Pt-(Ni-NiO)@C-1 catalyst prepared in this application has excellent HER activity under alkaline conditions.
[0065] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst, characterized in that: The steps include: S1. Pre-treating the carbon cloth to obtain a clean and hydrophilic surface; S2, uniformly dissolving Ni(NO3)2·6H2O in methanol to form solution 1; uniformly dissolving 2-methylimidazole in methanol to form solution 2; mixing solution 1 and solution 2 to obtain a mixed solution; wherein the dissolved concentration of Ni(NO3)2·6H2O in solution 1 is 0.1-0.4 mg / mL, the dissolved concentration of 2-methylimidazole in solution 2 is 0.05-0.2 mg / mL, and the mass ratio of Ni(NO3)2·6H2O to 2-methylimidazole in the mixed solution is (2-4):1; The carbon cloth pretreated in step S1 is immersed in the mixed solution, reacted at room temperature, taken out, washed and dried, and Ni(OH)2 nanosheets are in situ grown on the carbon cloth fibers; S3, the carbon cloth on which the Ni(OH)2 nanosheets are grown is treated with a carbon dioxide laser at a frequency of 25-40 KHz, a processing speed of 200-300 m / s, a line spacing of 0.1-1 mm, and a laser power of 3 W-12 W, to obtain Ni-NiO core-shell nanospheres on the carbon cloth fibers, wherein NiO is the shell and Ni is the core; S4. Immerse the carbon cloth on which Ni-NiO core-shell nanospheres are grown in an H2PtCl6 aqueous solution with a concentration of 0.2-0.5 mg / mL, an immersion temperature of 50-60 °C, and a time of 2-10 h. Then take out, wash and dry, and finally obtain a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst, in which Pt single atoms are loaded on Ni-NiO core-shell nanospheres to form Pt-(Ni-NiO) nanospheres, and the Pt-(Ni-NiO) nanospheres are loaded on carbon cloth fibers.
2. The method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst according to claim 1, characterized in that: In step S1, the carbon cloth is ultrasonically treated in acetone, ethanol and deionized water for 10-30 minutes in sequence, and then immersed in 2-6 M nitric acid for 10-20 hours to obtain a clean and hydrophilic surface.
3. The method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst according to claim 1, characterized in that: In step S2, 10.46 mg of Ni(NO3)2·6H2O was uniformly dissolved in 40 mL of methanol to form solution 1, 3.94 mg of 2-methylimidazole was uniformly dissolved in 40 mL of methanol to form solution 2, and solution 1 and solution 2 were mixed in a volume ratio of 1:1 to obtain a mixed solution.
4. The method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst according to claim 1, characterized in that: In step S2, the pretreated carbon cloth has a size of (1-3) cm*(3-6) cm, is immersed in 20-40 mL of the mixed solution, and reacts at room temperature for 12-24 h.
5. The method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst according to claim 1, characterized in that: The volume of the H2PtCl6 aqueous solution in step S4 is 6-10 mL.
6. The method for preparing a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst according to claim 1, characterized in that: In steps S2 and S4, deionized water is used for washing, and the drying temperature is 50-60° C. and the drying time is 12-20 hours.
7. A low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst obtained by the preparation method of a low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst as described in any one of claims 1 to 6.
8. Use of the low Pt-loaded Pt-(Ni-NiO) nanosphere@carbon cloth fiber catalyst according to claim 7 in hydrogen production by alkaline water electrolysis.
